2018
DOI: 10.1007/s00234-018-2088-z
|View full text |Cite
|
Sign up to set email alerts
|

Low rates of recanalization for wide-necked aneurysms treated with stenting after balloon-assisted coiling: combination of techniques delivers stable and improved results during follow-up

Abstract: Our results suggest that treatment of wide-necked aneuryms with stent placement after BAC yields low recanalization rates and enhanced angiographic outcomes in long-term follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…Stent-assisted coiling (SAC) represents an effective and safe treatment option for complex and broad-based intracranial aneurysms. Even though several innovative endovascular concepts such as extra-or intra-aneurysmal flow diverters or bifurcation stents were established during the last decade, SAC remains one of the most frequently applied techniques for wide-necked aneurysms [1][2][3][4][5]. The first stent intended for the treatment of wide-necked aneurysms approved by the FDA in 2002 was the Neuroform Microdelivery Stent System (Stryker, Kalamazoo, MI, USA) [6].…”
Section: Introductionmentioning
confidence: 99%
“…Stent-assisted coiling (SAC) represents an effective and safe treatment option for complex and broad-based intracranial aneurysms. Even though several innovative endovascular concepts such as extra-or intra-aneurysmal flow diverters or bifurcation stents were established during the last decade, SAC remains one of the most frequently applied techniques for wide-necked aneurysms [1][2][3][4][5]. The first stent intended for the treatment of wide-necked aneurysms approved by the FDA in 2002 was the Neuroform Microdelivery Stent System (Stryker, Kalamazoo, MI, USA) [6].…”
Section: Introductionmentioning
confidence: 99%
“…Another retrospective study by Velasco González et al ( 4 ) demonstrated low rates of recanalization for wide neck aneurysms treated with stenting after BRT, in 87 aneurysms of 80 patients treated between 2009–2012. This relatively old patient pool had long-term follow-up results.…”
Section: Discussionmentioning
confidence: 96%
“…There have been some literatures advocating BST ( 1 2 3 4 ). Some recent case reports demonstrated the feasibility of BST using a low-profile visualized intraluminal stent (LVIS Jr, Microvention, Tustin, CA, USA) with double lumen balloons in the treatment of middle cerebral artery (MCA) aneurysms ( 5 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…This may have resulted from balloon-assisted technique because the technique can enable denser packing of the aneurysm fundus and neck region or help mold the coil mass to improve its interface with the parent vessel. [24,25] Regarding the rate of stroke, this was almost 4%. Several factors may explain our low rate of stroke.…”
Section: Discussionmentioning
confidence: 99%